Concept Teaching in Science Classrooms: A Critical Discourse Analysis of Teachers' Talk - Mensure Alkis Kucukaydin (Seyit Ahmet Kıray, 2019)
Studies on science education stress that, in terms of discourse, teachers need to carefully build their understanding of science, language, and authority to better enable students to be successful in their science learning. However, the question of how much attention should be paid to this discourse, particularly for primary and middle-school students, remains controversial. This study examined the discourse of two teachers, who teach science at the primary and middle- school levels in different locations of Turkey, during concept teaching. The teachers' ideological structures related to social and pedagogical domains were analyzed through critical discourse analysis. The results revealed certain differences between the discourse of the teachers who teach at the primary and middle-school levels. Several factors, such as the patriarchal structure of the society and curriculum, lie at the bottom of these differences.